Analysing potential side-channel leakage on an embedded device - Lau, Li Hao (Nanyang Technological University, 2023)
AES, a widely used encryption technique, is used to safeguard sensitive data in a variety of applications. It is nevertheless susceptible to side-channel analysis (SCA) attacks, which try to take advantage of physical weaknesses in a cryptosystem by examining elements like time intervals, power usage monitoring, and electromagnetic emissions. It was shown in previous studies that certain lightweight embedded systems could be attacked via SCA, thus in this study, we seek to determine if the cryptographic keys used in AES encryption on a lightweight operating system (OS) like the Raspberry Pi (RPi) OS, can be retrieved from any side-channel leakage. To see if SCA is possible, we restrict the plaintext to 16 bytes and go through the encryption process numerous times. The report includes a review of the literature, hardware and software configurations for the experimental procedures, implementation and analysis of the results, and a conclusion with suggestions for future research. It will reveal that the SCA methods used in this research were insufficient to retrieve the encryption key and potential factors which may be attributed to this result. The study's conclusions will contribute to making lightweight systems' AES encryption more secure.